The ama-Male - O'Rourke, Paul F. (Zeitschrift für ägyptische Sprache und Altertumskunde, 2010)
An agreed upon meaning for the word ama (Wb. I 185, 13) has not yet been satisfactorily established. The present study is an examination and discussion of ama in the context of each text in which it appears. The author offers for consideration the specific meaning “ritually impure” for the term.